Manufacturing of poly(ethylene glycol diacrylate)-based hollow microvessels using microfluidics. Issue 7 (24th January 2020) - Aykar, Saurabh S.; Reynolds, David E.; McNamara, Marilyn C.; Hashemi, Nicole N.
Abstract : Biocompatible and self-standing poly(ethylene glycol diacrylate)-based hollow microvessels were fabricated from a microfluidic device using microfluidic principles. Abstract : The microvasculature is a vital organ that distributes nutrients within tissues, and collects waste products from them, and which defines the environmental conditions in both normal and disease situations. Here, a microfluidic chip was developed for the fabrication of poly(ethylene glycol diacrylate) (PEGDA)-based hollow self-standing microvessels having inner dimensions ranging from 15 μm to 73 μm and displaying biocompatibility/cytocompatibility. Macromer solutions were hydrodynamically focused into a single microchannel to form a concentric flow regime, and were subsequently solidified through photopolymerization. This approach uniquely allowed the fabrication of hollow microvessels having a defined structure and integrity suitable for cell culturing.